Crystal structure of the yeast heterodimeric ADAT2/3 deaminase - Xiwen Liu; Ruoyu Chen; Yujie Sun; Ran Chen; Jie Zhou; Qingnan Tian; Xuan Tao; Zhang Zhang; Guan-zheng Luo; Wei Xie (BMC Biology, 2020)
Abstract Background The adenosine-to-inosine (A-to-I) editing in anticodons of tRNAs is critical for wobble base-pairing during translation. This modification is produced via deamination on A34 and catalyzed by the adenosine deaminase acting on tRNA (ADAT) enzyme. Eukaryotic ADATs are heterodimers composed of the catalytic subunit ADAT2 and the structural subunit ADAT3, but their molecular assemblies and catalytic mechanisms are largely unclear. Results Here, we report a 2.8-Å crystal structure of Saccharomyces cerevisiae ADAT2/3 (ScADAT2/3), revealing its heterodimeric assembly and substrate recognition mechanism. While each subunit clearly contains a domain resembling their prokaryotic homolog TadA, suggesting an evolutionary gene duplication event, they also display accessory domains for additional structural or functional purposes. The N-lobe of ScADAT3 exhibits a positively charged region with a potential role in the recognition and binding of tRNA, supported by our biochemical analysis. Interestingly, ScADAT3 employs its C-terminus to block tRNA’s entry into its pseudo-active site and thus inactivates itself for deamination despite the preservation of a zinc-binding site, a mechanism possibly shared only among yeasts. Conclusions Combining the structural with biochemical, bioinformatic, and in vivo functional studies, we propose a stepwise model for the pathway of deamination by ADAT2/3. Our work provides insight into the molecular mechanism of the A-to-I editing by the eukaryotic ADAT heterodimer, especially the role of ADAT3 in catalysis.